Simulation of the spread of turnover intention behavior through employee interaction in a digital work environment - Sahasika Rahmalia Dewi; Dana Azizah Rahmat; Dhiyan Septa Wihara; Hafid Kholidi Hadi (Journal of Management Small and Medium Enterprises (SMEs), 2026)
Turnover intention has become an increasingly complex issue in digital work environments due to the combined influence of employees' psychological conditions and social interactions. This study aims to analyze the dynamics of turnover intention diffusion using an agent-based modeling (ABM) approach. The model was developed in NetLogo with 100 employee agents and incorporated digital work stress, job engagement, organizational commitment, interaction intensity, and digital work environment quality as key variables. Simulations were conducted for 96 ticks, representing 24 months, across three scenarios: digital work stress, social diffusion, and organizational commitment. The simulation results indicate that higher digital work stress consistently increases turnover intention, while job engagement and organizational commitment help reduce this tendency. Social interaction intensity significantly accelerates the spread of turnover intention through a contagion effect, resulting in faster diffusion within highly connected employee networks. Furthermore, organizational commitment acts as a protective factor that promotes positive emergent behavior by reducing turnover intention and maintaining organizational stability. These findings demonstrate that ABM effectively captures how individual behavioral changes evolve into collective organizational patterns and provides a valuable decision-support tool for evaluating employee retention strategies in digital work environments. Keywords: Agent-Based Model; Turnover Intention; Digital Work Environment; Social Contagion; Organizational Commitment